Short-term antidepressant treatment has long-lasting effects, and reverses stress-induced decreases in bone features in rats (2019)
Antidepressants are among the most-prescribed class of drugs in the world and though weight gain is a common outcome of antidepressant treatment, that effect is not well understood. We employed an animal model comprised of 2 weeks of chronic restraint stress with antidepressant treatment, followed by diet-induced obesity. We showed that short-term antidepressant treatment had long-lasting effects, not only leading to weight gain, but also enhancing trabecular and cortical bone features in rats; therefore, weight gain in this model was different from that of the classic diet-induced obesity. Late in the post-restraint recovery period, antidepressant-treated animals were significantly heavier and had better bone features than saline-treated controls, when assessed in the distal femoral metaphysis. The propensity to gain weight might have influenced the rate of catch-up growth and bone allometry, as heavier animals treated with fluoxetine also had enhanced bone features when compared to non-stressed animals. Therefore, short-term antidepressant treatment ameliorated the long-term effects of stress on body growth and bone. Growth and bone structural features were associated with leptin levels, and the interaction between leptin levels and antidepressant was significant for bone mineral content, suggesting that short-term antidepressants in the context of long-term diet-induced obesity modified the role of leptin in bone formation. To our knowledge this is the first study reporting that short-term antidepressant treatment has long-lasting effects in restoring the effects of chronic stress in body weight and bone formation. Our findings may be relevant to the understanding and treatment of osteoporosis, a condition of increasing prevalence due to the aging population. © 2019, The Author(s).